Sojourner Truth : ain't I a woman? - McKissack, Pat, 1944-2017; McKissack, Fredrick (New York : Scholastic, 1992)
A biography of the former slave who became well-known as an abolitionist and advocate of women's rights.
Hardenbergh's Belle -- Dumont's Belle -- Free Belle! -- Kingdom -- Gone forever -- New direction -- Ain't I a woman -- Keep 'Em scratchin -- Book of life -- Last cause.
Includes bibliographical references and index.
Keywords: Truth, Sojourner, -- 1799-1883 -- Juvenile literature; African American abolitionists -- Biography -- Juvenile literature; Abolitionists -- United States -- Biography -- Juvenile literature; Social reformers -- United States -- Biography -- Juvenile literature; Biography; Juvenile works